Effects of protein on fermentation and fiber disappearance in vitro using an equine cecal inoculum - Engelland, Ethan N.; Fehlberg, L.K.; Hurless, W.; Jones, Cassandra K.; Douthit, Teresa L.; Lattimer, James M. (My University, 2018)
The purpose of this experiment is to determine the effects of varying protein sources on in vitro fermentation characteristics and fiber disappearance utilizing an equine cecal fluid inoculum. Experimental design consisted of a completely randomized design with 4 replications (horse). Treatments consisted of protein source (no protein, casein, whey, soybean meal, plasma, L-lysine, and fishmeal). Cecal fluid was acquired from 4 cecally cannulated horses consuming a diet of smooth bromegrass hay (1.5% BW) and commercial concentrate (0.5% BW). Strain and stratified cecal fluid was mixed with McDougal’s buffer, substrates, and respective treatments and then incubated for 48 hours in a shaking incubator at 39°C. Gas pressure was continuously recorded and terminal concentrations of DM, OM, NDF, ADF, and VFA (acetate, propionate, butyrate, Valerate and Isovalerate) were determined. Compared to the control, casein, soybean meal, whey, plasma, L-lysine, and fishmeal increased (P < 0.05) DM disappearance and acetate production. NDF and ADF disappearance was greater (P < 0.05) for all protein sources when compared to control. Total VFA concentrations increased (P < 0.05) with all protein sources when compared to the control. Results from this experiment demonstrate that fiber disappearance of a low quality can be enhanced via supplemental protein, regardless of source. Similarly, protein increases VFA production which can be attributed to greater microbial activity and/or populations. Protein sources with greater solubility appear to be more effective at improving fiber disappearance and VFA production although this observation was not statistically significant. Future work in vivo is warranted to determine if the same effects would be observed in the equine.
Keywords: Spring 2018